Aviation education in the middle east: sustaining growth and indigenous development. (5th July 2005) - Rhoades, Dawna L.; Petree, Daniel
The middle east, particularly the gulf coast region, is experiencing a major growth in both airlines and airport infrastructure. At the present time, much of this growth is being sustained through the use of expatriates that make up from 20–60% of the total workforce in this region. While there are a number of programmes in higher education aimed at the aviation/aerospace industry, most are in Western nations and the flow of middle eastern students into these programmes has been severely limited by the events of September 11. This paper examines regional needs in aviation education and efforts to meet them through the establishment of local centres of aviation education.